Occurrence and Characterization of a Phosphoenolpyruvate: Glucose Phosphotransferase System in a Marine Bacterium, Serratia marinorubra - Hodson, Robert E. (1979)
The mechanism of d-glucose transport in the marine bacterium Serratia marinorubra was investigated. Uptake is mediated by a single, constitutive phosphoenolpyruvate:sugar phosphotransferase system (PTS), resulting in phosphorylation of d-glucose to d-glucose phosphate during transport. The system is saturable (K(m) = 6.4 × 10(−6) M) and highly temperature dependent, with a Q(10) of 3.5 between 5 and 15°C. The system is highly specific for d-glucose; structurally related sugars and sugar alcohols did not significantly compete with d-glucose for transport. The PTS requires Mg(2+) (K(m) = 2.5 × 10(−4) M), but its activity is otherwise unaffected by salinity changes over the range tested (0 to 35 ‰). S. marinorubra differs from other gram-negative organisms (Escherichia coli and Salmonella typhimurium) in that its glycerol (non-PTS substrate) permease is not regulated by the presence of glucose (PTS substrate).